bHLH003, bHLH013 and bHLH017 are new targets of JAZ repressors negatively regulating JA responses. - Sandra Fonseca; Patricia Fernández-Calvo; Guillermo M Fernández; Monica Díez-Díaz; Selena Gimenez-Ibanez; Irene López-Vidriero; Marta Godoy; Gemma Fernández-Barbero; Jelle Van Leene; Geert De Jaeger; José Manuel Franco-Zorrilla; Roberto Solano (PLoS ONE, 2014)
Cell reprogramming in response to jasmonates requires a tight control of transcription that is achieved by the activity of JA-related transcription factors (TFs). Among them, MYC2, MYC3 and MYC4 have been described as activators of JA responses. Here we characterized the function of bHLH003, bHLH013 and bHLH017 that conform a phylogenetic clade closely related to MYC2, MYC3 and MYC4. We found that these bHLHs form homo- and heterodimers and also interact with JAZ repressors in vitro and in vivo. Phenotypic analysis of JA-regulated processes, including root and rosette growth, anthocyanin accumulation, chlorophyll loss and resistance to Pseudomonas syringae, on mutants and overexpression lines, suggested that these bHLHs are repressors of JA responses. bHLH003, bHLH013 and bHLH017 are mainly nuclear proteins and bind DNA with similar specificity to that of MYC2, MYC3 and MYC4, but lack a conserved activation domain, suggesting that repression is achieved by competition for the same cis-regulatory elements. Moreover, expression of bHLH017 is induced by JA and depends on MYC2, suggesting a negative feed-back regulation of the activity of positive JA-related TFs. Our results suggest that the competition between positive and negative TFs determines the output of JA-dependent transcriptional activation.